Analysis and design of a composite left-/right-handed leaky wave antenna based on the H10 rectangular waveguide mode - T. F. Eibert; Y. Weitsch (Advances in Radio Science, 2008)
The presented "open" composite left-handed/right-handed (CRHLH) substrate integrated waveguide performs well as a low-profile leaky wave antenna. This design is distinguished due to the fact that it is derived from the approved equivalent circuit model of the H10 rectangular hollow waveguide mode. The wave propagation behaviour is visualised by the dispersion diagram calculated by two different methods, infinite periodic full-wave simulation and Matrix-Pencil analysis of driven field solutions. The periodic configuration is also analysed in terms of the Bloch impedance. Although FR-4 serves as substrate the antenna features an efficiency of about 50% to 60%. The radiation performance demonstrates nearly backfire to almost endfire scanning capability of the antenna by mere frequency variation. Broadside radiation is possible due to the balanced state at 4 GHz.